Occupational stress in criminal police: study in a prison unit in Minas Gerais - Campos, Rafaela Gonçalves; Abreu, Arlete Aparecida de; Souto, Sarah Lopes (Revista de Administração da UFSM, 2022)
Purpose: The objective of this work was to identify the levels of occupational stress in Criminal Police, as well as their generating factors (stressors), coping strategies and suggestions for improvement. Design/methodology/approach: Based on a quantitative study carried out in a Prison Unit in Minas Gerais, data were collected through an electronic questionnaire, adapted from the Theoretical Model for Explanation of Occupational Stress (MTEG) developed and validated by Zille (2005). The results were analyzed using univariate and multivariate statistics and the discursive questions were treated from the Content Analysis Findings: The main results indicate that 89% of those surveyed present stress ranging from mild to moderate to very intense and the main stressors are related to the insufficient number of staff, the biological risk of infectious diseases, overcrowding and high risk of detainees, in addition to the relationship with colleagues and management. It is also worth mentioning improvement actions aimed at 3 categories: Public Power, Management and Servants. Research limitations/implications (if applicable): It is worth noting the fact that it was carried out only in a prison unit and the impossibility of interviews, in view of the restrictions imposed by the Covid 19 Pandemic. Practical implications: The study highlights suggestive actions that involve the government, the direction of the Unit and also the Criminal Police in an attempt to collaborate to reduce the level of stress experienced by servers. In addition to the clamor for an increase in the number of employees, the valorization of work, dialogue, training are some of the practical actions to be taken. Social implications: It is believed that the research draws attention to variables that influence the level of security, both of the agents and the community. Therefore, it is a matter of collective interest. Originality/value (mandatory): We sought to contribute to the advancement of research on stress at work carried out by Criminal Police, pointing out the main stress-generating factors and indications of improvements, from the perspective of those involved. In this way, it contributes with information that can help the management of prisons, as well as justify more solid public actions for the category.